2002
DOI: 10.1034/j.1600-051x.2002.290504.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal diseases in the child and adolescent

Abstract: This paper reviews the current literature concerning the most common periodontal diseases affecting children: chronic gingivitis (or dental plaque-induced gingival diseases) and early onset periodontitis (or aggressive periodontitis), including prepubertal and juvenile periodontitis. In addition, systemic diseases that affect the periodontium and oral lesions commonly found in young children are addressed. The prevalence, diagnostic characteristics, microbiology, host-related factors, and therapeutic managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
177
1
32

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(212 citation statements)
references
References 97 publications
2
177
1
32
Order By: Relevance
“…Plaque-induced chronic gingivitis in children can be managed by mechanical removal of plaque and good oral hygiene 20 and good hygiene should have further benefits in terms of caries risk. Dental practitioners and other members of the dental team have an important role in developing effective hygiene practices at an early stage through education of parents and children.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque-induced chronic gingivitis in children can be managed by mechanical removal of plaque and good oral hygiene 20 and good hygiene should have further benefits in terms of caries risk. Dental practitioners and other members of the dental team have an important role in developing effective hygiene practices at an early stage through education of parents and children.…”
Section: Discussionmentioning
confidence: 99%
“…1 It was demonstrated that prevalence, extent and severity of gingivitis increase with age, starting in the primary dentition and reaching their peak during adolescence. 2,3 Gingivitis in children was also shown to be less severe compared to adults when similar amounts of plaque deposition are found. However, the same gingival indices have been used to diagnose the gingival status in children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Las enfermedades periodontales se encuentran entre las dolencias más frecuentes que afectan a los niños y adolescentes [1][2][3][4] . El nivel de higiene oral en la mayoría de los jóve-nes es regular, y una higiene oral deficiente es uno de los factores de riesgo responsables de caries y enfermedad periodontal, ambas altamente prevalentes en Chile 5,6 .…”
Section: Introductionunclassified